2018
DOI: 10.1080/01443615.2017.1417979
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of interstitial pregnancies: experience of a single centre

Abstract: The aim of this study was to compare the effect of local intracavitary methotrexate (MTX) injection and laparoscopic (L/S) cornuostomy in the treatment of interstitial pregnancy (IP) in terms of clinical and reproductive outcome. The data of patients with IP (n:10) who were treated between September 2011 and December 2016 with either an intra-amniotic MTX injection (n:7) or L/S cornuostomy (n:3) were retrospectively evaluated. All cases (7/7) in the local injection group and two (2/3) in the L/S group were suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Uludag et al reported successful local methortrixacate (MTX) treatment in 7 cases and successful laparascopic cornuostomy in the remaining 3 cases. The success rate was not different between the local MTX and laparascopy groups (100% vs. 66.6%, p > .05) (14). In her case series published in 2018, Dagar et al presented successful treatment of cornual pregnancy with methotrexate injection (15).…”
Section: Discussionmentioning
confidence: 91%
“…Uludag et al reported successful local methortrixacate (MTX) treatment in 7 cases and successful laparascopic cornuostomy in the remaining 3 cases. The success rate was not different between the local MTX and laparascopy groups (100% vs. 66.6%, p > .05) (14). In her case series published in 2018, Dagar et al presented successful treatment of cornual pregnancy with methotrexate injection (15).…”
Section: Discussionmentioning
confidence: 91%
“…MTX therapy has been shown to be effective. 18,19 However, for cases with large mass in diameter > 20 mm 18 and high serum β-hCG levels, 19 MTX therapy is likely to fail. Some researchers have reported their practices of hysteroscopic procedure with/or without laparoscopic assistant.…”
Section: Discussionmentioning
confidence: 99%
“…MTX therapy has been shown to be effective 18,19 . However, for cases with large mass in diameter > 20 mm 18 and high serum β‐hCG levels, 19 MTX therapy is likely to fail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cornuostomy is an attractive alternative to cornual resection because it preserves the normal uterine myometrium [14].…”
Section: Introductionmentioning
confidence: 99%